PERKEMBANGAN BIOFILM NITRIFIKASI DI FIXED BED REACTOR PADA SALINITAS TINGGI - Sudarno, Sudarno (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2012)
Development of nitrification biomass that is growing attached on carried material was examined by measuring its ammonium or nitrit oxidation rates. Porous ceramic rings (36 pieces) were put into the fixed bed reactor (FBR ). The fixed bed reactorÂ  that was operated continuously for more than 500 day was continued to be operated at a HRT of 1 day, a DO of above 5 mg L-1 and pH of 8. Ammonia concentration in the feeding was 50 mg NH4+-N L-1.Â  At days 1, 5, 12, 20, 33 and 50, six porous ceramic rings were taken out and then ammonia and nitrite removal rate by biofilm in the ceramic rings was separately measured. The measurement of rates was done in small cylindrical glass reactors with initial concentration of ammonia and nitrite was 10 mg N L-1. Until 50 days of incubation AORs were always higher than NORs. Additionally, ammonia oxidizers attach or grow faster in the porous ceramic material than nitrite oxidizers. Keywords: saline wastewater, Ammonium Oxidizing Bacteria, Nitrit Oxidizing Bacteria, biofilm